Social transfers in times of economic distress: the example of Bulgaria - Zahariev, Boyan (Ревија за социјална политика/Journal of Social Policy, 2013)
The article looks at how the system of social transfers in Bulgaria responded to the macroeconomic shocks coming from the global economic crisis. Several channels for the transfer of shocks are discussed looking at the specific impact on the Roma and Turkish populations, which are particularly vulnerable. The main data used come from three waves of a panel crisis monitoring survey carried out by the World Bank and the Open Society Institute – Sofia but other sources such as data from several surveys of the National Statistic Institute are used as well. The role of social transfers needs to be examined in a broader policy context, as the response of the system can only be understood at the background of the longer trends in the shaping and reshaping of the system of social transfers towards а workfare approach and the interaction of this system with other policies, which are key to lowering social disparities such as taxation, employment policy and the labour market regulation. The global economic crisis worked as a stress test for the weaknesses in social cohesion policies and the social transfers in particular. The main conclusion is that its impact on relative poverty in Bulgaria was moderate in international comparison due mainly to the pension system and with very little contribution from other social transfers. The at-risk-of-poverty rate even somewhat decreased but this was not due to any real improvement but to the fact that this indicator is not very good for capturing poverty in times of recession. On the long run however the current system of social transfers in Bulgaria does not offer any instruments to adequately address poverty and social exclusion. Bulgaria’s exit from the economic crisis proved to be longer than anyone could expect at the beginning. Bulgaria, unlike many of the EU countries, was following a policy of pre-emptive austerity. Dismantling parts of the social protection system was part of the strategy to exit from the crisis. This may not be the right way to catch up with the leading EU countries in terms of the quality of life.